SERVICE PERFORMANCE OF THE OFFICE LAND TAPIN DISTRICT IN MAKING LAND CERTIFICATE - Arlan, Agus Sya'bani (stiatabalong.ac.id, 2019)
This study aims to describe the performance of the services, analyze the factor restricting services and interpret the models performance Office land District Tapin. This research uses qualitative research methods with the descriptive approach. Research analysis unit is the Office of the District Land Commission Tapin, with data collection techniques are observation, interview, and documentation.             The results showed that the performance of the District Land Office Tapin in improving  registration  of land rights according to commendation Agrarian Staple ACT No. 5 of 1960 concerning the  basic rules of agrarian issues and PP RI Number 24 in 1997 about the land registry, are: (1) in the field of land administration  serve does no go well, and (2) less than optimal in the socialization of land areas.             On the basis of research results, in order to improve the performance of the District Lnd Office Tapin and registration of land, then the Government should implement the socialization or outreach to the public through print and electronic media. As well as increasing the budget costs of organizing land rights en masse at no cost, and revamping the regulations concerning land rights to article that is forced by the sanctions firmly to the landowners who have yet to register their land rights. Keywords: performance; service; making land certificates